Ekranisasi Novel Dignitate Karya Hana Margaretha ke Film Dignitate Sutradara Fajar Nugros - Lailatul Amal; Emilda Rani; Ardesa Pratiwi (Global Action and Education for Society, 2026)
This study aims to describe the ecranization of Hana Margaretha's novel